Recent Advances in Transition-Metal Based Nanomaterials for Noninvasive Oncology Thermal Ablation and Imaging Diagnosis - Peng, Qiuxia; Qian, Zhangbo; Gao, Huali; Zhang, Kun (Frontiers in Chemistry, 2022)
With the developments of nanobiotechnology and nanomedicine, non-invasive thermal ablation with fewer side effects than traditional tumor treatment methods has received extensive attention in tumor treatment. Non-invasive thermal ablation has the advantages of non-invasiveness and fewer side effects compared with traditional treatment methods. However, the clinical efficiency and biological safety are low, which limits their clinical application. Transition-metal based nanomaterials as contrast agents have aroused increasing interest due to its unique optical properties, low toxicity, and high potentials in tumor diagnosis. Transition-metal based nanomaterials have high conversion efficiency of converting light energy into heat energy, good near-infrared absorption characteristics, which also can targetedly deliver those loaded drugs to tumor tissue, thereby improving the therapeutic effect and reducing the damage to the surrounding normal tissues and organs. This article mainly reviews the synthesis of transition-metal based nanomaterials in recent years, and discussed their applications in tumor thermal ablation and diagnosis, hopefully guiding the development of new transition metal-based nanomaterials in enhancing thermal ablation.